Analysis and implementation of power management and control strategy for six-phase multilevel ac drive system in fault condition - Padmanaban, Sanjeevikumar; Grandi, Gabriele; Blaabjerg, Frede; Wheeler, Patrick; Ojo, Joseph Olorunfemi (Elsevier, 2016)
This research article exploits the power management algorithm in post-fault conditions for a six-phase (quad) multilevel inverter. The drive circuit consists of four 2-level, three-phase voltage source inverter (VSI) supplying a six-phase open-end windings motor or/impedance load, with circumstantial failure of one VSI investigated. A simplified level-shifted pulse-width modulation (PWM) algorithm is developed to modulate each couple of three-phase VSI as 3-level output voltage generators in normal operation. The total power of the whole ac drive is shared equally among the four isolated DC sources. The developed post-fault algorithm is applied when there is a fault by one VSI and the load is fed from the remaining three healthy VSIs. In faulty conditions the multilevel outputs are reduced from 3-level to 2-level, but still the system propagates with degraded power. Numerical simulation modelling and experimental tests have been carried out with proposed post-fault control algorithm with three-phase open-end (asymmetrical induction motor/R-L impedance) load. A complete set of simulation and experimental results provided in this paper shows close agreement with the developed theoretical background.